2019
DOI: 10.1021/jacs.9b08541
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer in a Radical SAM Enzyme Generates an S-Adenosylmethionine Derived Methyl Radical

Abstract: Radical SAM (RS) enzymes use S-adenosyl-L-methionine (SAM) and a [4Fe-4S] cluster to initiate a broad spectrum of radical transformations throughout all kingdoms of life. We report here that low-temperature photoinduced electron transfer from the [4Fe-4S] 1+ cluster to bound SAM in the active site of the hydrogenase maturase RS enzyme, HydG, results in specific homolytic cleavage of the S-CH 3 bond of SAM, rather than the S-C5′ bond as in the enzymecatalyzed (thermal) HydG reaction. This result is in stark con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
56
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 86 publications
(192 reference statements)
5
56
2
Order By: Relevance
“…This generates a . CH 3 radical in the active site, as characterized by electron paramagnetic resonance (EPR) spectroscopy [29] . We found that this .…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…This generates a . CH 3 radical in the active site, as characterized by electron paramagnetic resonance (EPR) spectroscopy [29] . We found that this .…”
Section: Introductionmentioning
confidence: 81%
“…Reduced HydG with SAM bound to the [4Fe‐4S] + cluster furthermore undergoes cryogenic photoinduced electron transfer from the cluster to SAM, resulting in regiospecific cleavage of the S−CH 3 bond, rather than the S−C5′ bond (as in the case of PFL‐AE) [29, 30] . This generates a .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations